KELIMPAHAN, KEANEKARAGAMAN DAN SPESIES KHAS DARI KUMPULAN FORAMINIFERA BENTIK PADA SEDIMEN PERMUKAAN DASAR LAUT DI PERAIRAN TAMBELAN - Isnaniawardhani, Vijaya; Muhammadsyah, Faizal (Fakultas Teknik Geologi Universitas Padjadjaran, 2015)
Thirty-five surficial sediment samples in Tambelan Seas were studied to identify foraminifera assemblages in the sediments as marine resources. Samples were collected from the strait to the open sea (<100 m), coral reefal (<12 m), sandy beaches and mangrove. Benthic foraminifera assemblages classified in 58 genera of suborder Textulariina, Spirillinina, Miliolina, Lagenina, Buliminina, and Rotaliina. Sub-ordo Textulariina was represented by genera Ammobaculites, Dorothia, Karreriella, Bigerina, Sahulia, Textularia, and Clavulina. Genus Spirilliina is included in the sub-ordo Spirillinina. Genera Adelosina, Nummulopyrgo, Spiroloculina, Agglutinella, Ammomassilina, Lachlanella, Quinquelo-culina, Miliolinella, Pyrgo, Triloculina, Peneroplis, and Marginopora were classified into Suborder Miliolina. Suborder Lagenina was represented by genus Lagena, Guttulina, Oolina, Fissurina and Glandulina; whereas Suborder Buliminina by genus Bolivina, Siphogenerina, and Reussella. Genus Cancris, Valvuli-neria, Eponides, Orbitina, Neoconorbina, Rosalina, Siphoninoides, Discorbia, Lobatula, Planorbulinella, Cymbaloporella, Cymbaloporetta, Gypsina, Epistomaroides, Amphistegina, Nonionoides, Heterolepa, Gyroidina, Hanzawaia, Pararotalia, Rotalia, Ammonia, Asterorotalia, Pseudorotalia, Baculogypsinoides, Calcarina, Elphidium, Parrellina, Assilina, and Heterostegina included in Suborder Rotaliina. Some broken milliolidae can’t be determined. Surficial sediments on open sea generally content a high number of individu as well as high diversity; Sub-ordo Rotaliina dominated. Benthic foraminifera are abundant on reefal, decreased on sandy beach, while are rare in magrove swamp. Benthic foraminifera near reef showed higher diversity than sandy beach and mangove swamps. Amphistegina lessonii was recorded on open marine and coral reefal sediments around Tambelan archipelago. Assilina ammonoides is typical species in open marine; Calcarina calcar in coral reefal; and in contrast, these species were not founded on the sandy beach and mangrove swamps. Abundancy, diversity and appearance of typical species were influenced environment factors as depth/bathimetry, water supply, temperature, sunlight intensity, substrate/sediment type, turbidity, wave and current. The study result is very useful as a reference of benthic foraminifera taxonomy in Indonesia.